Surgical Management of the Armored Brain: Case Report of the Treatment of a Chronic Calcified Subdural Hematoma - Girotto, André Luiz; Gago, Guilherme (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Calcified chronic subdural hematomas (CCSDHs) are rare entities, whose yearly incidence ranges from 1.72 to 20.6 per every 100 thousand persons. Several different approaches to their management are reported in the literature, ranging from conservative treatment to craniotomy with full removal of the neomembranes. Currently, there are no guidelines or consensus that establish the best technique. We herein report a case of symptomatic CCSDH initially drained through a burr-hole craniotomy, with no resolution of the symptoms. Later, our patient underwent a craniotomy and partial membranectomy, which resulted in full symptomatic recovery.
Keywords: neurosurgery; chronic subdural hematoma; pathologic calcification